Mentoring communication practices and their relationship with study performance - Azman Ismail; Najihah Omar; Nor Ain Abdullah (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2017)
According to the recent literature connecting to institutions of higher learning, mentoring communication practices have two important features: interpersonal communication and communication openness. These communication practices may lead to an improved mentees’ study performance. Although many studies have been done, the role of mentoring communication practices as an essential determinant has been left unexplained in the institutions of higher learning research literature. Therefore, this study was undertaken to examine the effect of mentoring communication practices on study performance. A survey method was employed to collect selfadministered questionnaires from undergraduate accounting, economics and management students at a public research university in Malaysia. The results of SmartPLS path model analysis demonstrate that interpersonal communication does not act as an essential determinant of mentees’ study performance, while communication openness does act as an essential determinant of mentees’ study performance in the organizational sample. Additionally, this study offers discussion, implications and conclusion.